MULTIKULTURALISME: ANALISIS WACANA BUKU TEKS PELAJARAN SEJARAH - Syahriman, Agung; Mulyana, Agus (Jazirah: Jurnal Peradaban dan Kebudayaan, 2021)
This article is a review of the history textbooks of High School that aims to view and analyze the content of multiculturalism material contained in history textbooks. The method used in this study is critical discourse analysis. The subject in this study is Indonesia history textbook class XI High School Curriculum 2013 (Revised 2017). The results of the study showed that there is a content of multiculturalism material contained in textbooks. This can be seen from the achievements of indoctrinators who support multiculturalism as a whole (the value of tolerance, the value of equality, and democratic values). With the appearance of these indicators, it can be said that the Indonesia history textbook class XI curriculum 2013 is enough to display the content of material containing multiculturalism. In addition, withthe ampilnya content of multiculturalism material in historical textbooks, it can be said to be an effort to be able to channel the understanding of multiculturalism to the younger generation (students). The material of multiculturalism itself is very suitable to be displayed in historical textbook material. Because, history textbooks in addition to being a medium that supports learning, is also a medium that can show learners a historical event that has occurred in the past with many essences and values of diversity that exist. It is a common interest for the formation of attitudes of learners who can respect each other in their lives.